Worldview approach to resolution of information security problems in the context of information society formation and systemic crisis in the world - Bondarenko, V. M. (Journal of Economic Research & Business Administration, 2015)
The article substantiates the argument that as a result of broad proliferation of info-, gene cognitive and nano-technologies, as well as virtual reality, DNA molecule-based bio-computers, etc., and, at the same time, development of the global systemic crisis that encompassed all facets of the human community life made it hardly if ever possible to provide information security and, even more, peace and security for different countries, regions, municipal formations and all sorts of people in the multinational society. In order to identify proper conditions for further development and construction of information society as well as guaranteed peace and information security we applied the new methodological “tool-kit” that made it possible to reveal the objective causes of the global systemic crisis and to fi nd the paths to take the crisis-free development road. Also, the article amply shows the need to proceed to the relevant humancommunity life organization model that would not run counter to science-tech attainments of the 21st century.